(untitled) (Research, Society and Development, 2021)
This study aimed to analyze stages and methods of planning, team profile and menu of offers of psychosocial e-therapies produced for promotion and support in mental health, during the COVID-19 pandemic, through an Action Research (P-A). This is a documental analysis of the proposed project and action plans, content of recordings of team meetings made available through the Google Meet digital platform and the records of the following digital tools: Slack, Trello and WhatsApp groups, during the period from May 7, 2020 to March 4, 2021. The team participated in the team, including researchers and students from two public higher education institutions and mental health professionals, from different services of public health care and social development networks in Brazil. The results are described from the following themes: formation of the multidisciplinary team; development trajectories of P-A: stages and methods; menu of offers of psychosocial actions. A total of 15 e-therapy modalities were offered, in the form of therapeutic groups, mostly lasting from 2 to 3 months. Thus, the study gives evidence of important psychosocial support tools to different audiences and the relevance of the multiprofessional, transdisciplinary and dialogical character in the development of its stages, much needed in mental health support offerings, in times of pandemic and post-pandemic.